An innovative multi-parameter fusion compensation algorithm for ZRO drift of MEMS gyroscope under full-temperature conditions - Wang, Jianpeng; Yang, Gongliu; Liu, Fumin; Cai, Qingzhong; Song, Ningfang; Zhou, Yi (Measurement : journal of the International Measurement Confederation, 2026)
The performance of micro-electromechanical system (MEMS) gyroscopes is profoundly influenced by temperature. In this study, a novel approach is proposed to enhance the thermal performance of MEMS gyroscopes by compensating for the zero-rate output (ZRO) temperature drift error through internal multi-parameter fusion calibration, without the need for additional temperature sensors. This method is applicable to all MEMS gyroscopes currently under investigation. The relationships between the ZRO temperature drift error and key gyroscope parameters — including drive mode resonant frequency, drive excitation voltage, quadrature suppression voltage, and reference source voltage — were analyzed, based on these relationships, a mathematical model for the full-temperature-range ZRO temperature drift error was established. By performing multi-parameters linear fusion compensation of ZRO using these four parameters, the temperature performance of ZRO was markedly improved. Experimental results demonstrate that, within the temperature range of -40 °C to 60 °C, the peak-to-peak value of ZRO was reduced from 0.7965°/s to 0.1168°/s, representing an 85% decrease. In comparison to single-parameter compensation using drive mode resonant frequency, drive excitation voltage, quadrature suppression voltage, and reference source voltage, wherein peak-to-peak values were reduced from 0.3916°/s, 0.3881°/s, 0.2028°/s, and 0.4174°/s to 0.1168°/s, multi-parameter fusion compensation achieved reductions of 70%, 70%, 42%, and 72%, respectively. Furthermore, full-temperature-range bias stability improved by an order of magnitude, decreasing from 0.301°/s to 0.022°/s after compensation. •Proposes an innovative multi-parameter fusion method for compensating gyroscope zero rate output (ZRO).•Analyzes parameters causing gyroscope ZRO errors, and identifies error sources and compensation approaches.•Experimentally verifies the effectiveness and superiority of the proposed ZRO compensation method.